외적 인센티브와 사회적 선호가 분리배출 행동에 미치는 영향 - 현지은; Jieun Hyun; 최민식; Minsik Choi (환경정책, 2023)
본 연구에서는 사회적 선호(social preferences)가 개인의 분리배출 행동에 미치는 영향을 파악하기 위해 한국종합사회조사(KGSS) 데이터를 사용하여 로지스틱 회귀 분석을 실시하였다. 또한 금전적 동기(incentives)가 활용된 정책 모형에 행동경제학에서 강조하는 사회적 선호 변수를 추가함으로써 친환경 행동을 유도하는 정책의 순 효과를 파악하고자 하였다. 분석 결과, 사회적 선호를 통제하지 않는 경우 정책의 기대효과가 과소 혹은 과대 추정될 수 있는 것으로 나타났다. 이러한 연구 결과는 개인의 친환경 행동을 정확히 파악하기 위해서 전통 경제학에서 고려되는 선호 이외에 사회적 선호를 함께 고려해야 할 필요성을 시사한다. Our aim in this study is to understand the implications of social preferences for environmental policies such as Pigouvian taxes. We investigated the impact of social preferences on individuals’ participation in recycling, using KGSS data. To estimate the net effects of the related policies, we analyzed the interactions between the variables of pecuniary incentives emphasized in traditional economics and the variables of social preferences suggested by behavioral economics. We found that policies to alter individuals’ monetary incentives cannot be evaluated properly if the associated social preferences are not considered at the same time, which suggests that social preferences must be incorporated in the design and evaluation of such policies.